2015
DOI: 10.1017/s1041610215001210
|View full text |Cite|
|
Sign up to set email alerts
|

Mental health implications for older adults after natural disasters – a systematic review and meta-analysis

Abstract: Given the global rise in the number of older adults affected by natural disasters, mental health services need to be prepared to meet their needs following natural disasters, particularly around the early detection and management of PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(75 citation statements)
references
References 32 publications
5
61
0
3
Order By: Relevance
“…The interventions were also effective in treating and reducing the survivors' PTSD symptoms like anxiety and depression, and also in enhancing their psychological resilience [35,36,38,39]. These findings are consistent with previous results from a broad systematic literature review and meta-analysis studies that similarly explored the different rehabilitation interventions, services and outcomes in post-earthquake settings, and those following other disasters within and outside China [2,[13][14][15]43,44,[48][49][50][51][52]. Encouragingly, some of the HRR programs after the 2008 Wenchuan earthquake, such as physical and physiological rehabilitation, commenced within the first 5 months after the earthquake, which is commendable and helped to ameliorate long-term impacts such as injuries and PTSD from turning into acute problems for survivors that would prevent them from returning to normal life.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The interventions were also effective in treating and reducing the survivors' PTSD symptoms like anxiety and depression, and also in enhancing their psychological resilience [35,36,38,39]. These findings are consistent with previous results from a broad systematic literature review and meta-analysis studies that similarly explored the different rehabilitation interventions, services and outcomes in post-earthquake settings, and those following other disasters within and outside China [2,[13][14][15]43,44,[48][49][50][51][52]. Encouragingly, some of the HRR programs after the 2008 Wenchuan earthquake, such as physical and physiological rehabilitation, commenced within the first 5 months after the earthquake, which is commendable and helped to ameliorate long-term impacts such as injuries and PTSD from turning into acute problems for survivors that would prevent them from returning to normal life.…”
Section: Discussionsupporting
confidence: 83%
“…Earthquakes, like any other disasters, are traumatic events and they result in a range of physical, mental and psychological health consequences [2,8,[12][13][14][15]43,[50][51][52]56]. Indeed, this is attested to in the results of six studies in our systematic review [35][36][37][38][39]41]-which showed a high prevalence of PTSD among the different groups of survivors of the 2008 Wenchuan earthquake.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A general (non spatial) explanation for this may be that populations at risk (e.g. those with predisaster psychopathology, or those with higher peri-event emotional reactions) are more likely to experience postdisaster mental health problems4539. From our findings, we may assume that in specific situations, i.e., when specific individual- and community-level factors work together, this risk may increase.…”
Section: Discussionmentioning
confidence: 73%
“…Fourth, the clusters and point locations were mapped in the geographical information system QGIS3839.…”
Section: Methodsmentioning
confidence: 99%